Desenho contextual: uma abordagem fenomenológico- existencial ao problema da intervenção e restauro em lugares especiais feitos pelo homem - Flavio de Lemos Carsalade (2007)
The Architectural Restoration has been traditionally conceived as an issue of the visual arts and history/ archeology. This thesis main objective is to demonstrate that the principles related to the visual arts are not universally applied to architectural matters because of the specific nature of Architecture that implies the dimensions of use,articulated space, place and a specific social function as well. Besides, Architecture in its patrimony mode can not separate itself of daily life and the context where it is. So, this thesis works at the issue of the interventions at notable pre-existents spaces by means of phenomenology, hermeneutics and the existential based architectural theory.